EVALUASI SARANA DAN PRASARANA SOP PELAKSANAAN PROGRAM GEBRAK (GERAKAN BERSAMA AMANKAN KEHAMILAN DAN PERSALINAN) SEBAGAI UPAYA MENURUNKAN AKI DAN AKB DI DESA BANJARDOWO PULO LOR KABUPATEN JOMBANG : The Evaluation of Facilities and Infrastructure Standart Operating Procedure Gebrak (Joint Movement for Pregnancy and Labor Safety) Program Implementation as An Effort to Reduce Maternal Mortality Rate Rate in Banjardowo Pulo Lor Jombang District - Tri Ani Marwati; Dhesi Ari Astuti; Evi Rosita (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2020)
The MDGs ended 2015, and it is continued by the SDGs until 2030. The third Goal for the "Good Health and Well Being" indicator reduced MMR. Indonesia becomes the highest country for Maternal Mortality Rate in the ASEAN region. MMR in Indonesia 2012 reached 359,000 /100,000 KH meanwhile MM in East Java in 2015 reached 89.6 / 100,000 KH. In Jombang Regency in 2017 there were 28 maternal deaths. The action plan for reducing MMR is called GEBRAK program which began in 2016. The aim of the study was to evaluate the implementation of GEBRAK program as an effort to reduce MMR and IMR in Banjardowo Jombang Regency. This research employed qualitative study with in-depth interviews and documentation. The main research subjects were 8 teams (2 students, 2 midwives, 3 cadres, and 2 pregnant women). Supporting informants were 2 people (KGM Head Office and Head of Midwifery Diploma Program). Data was collected by in-depth interviews. Processing and analysis of data used content analysis. The results of the study showed that there was a program implementation policy in Health Office of East Java Province; complete facilities were available, human resources were community based team; budgets from the central and regional government was available; there was no similar, standardized and legalized SOPs; there was no reports written to Jombang Health Office, and the babies and mothers were healthy and safe. Jombang District Health Office is expected to arrange GEBRAK SOP with health education institutions, authorizes SOPs, disseminates SOPs, and monitors evaluations.